1989
DOI: 10.1037/0012-1649.25.3.439
|View full text |Cite
|
Sign up to set email alerts
|

Deception in 3-year-olds.

Abstract: Children's ability to deceive was examined in order to determine whether they are able to hide their emotional expression intentionally. Three-year-oids were instructed not to peek at a toy while the experimenter left the room. When asked, the great majority either denied that they peeked or would not answer the question. Facial and bodily activity did not differentiate the deceivers from the truth tellers. Boys were more likely than girls to admit their transgression. These results indicate that very young ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
327
6
9

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(366 citation statements)
references
References 21 publications
23
327
6
9
Order By: Relevance
“…Children as young as 3 exhibit some use of display rules (e.g., Cole, 1986), with girls doing so more frequently than boys (e.g., Davis, 1995). Relatedly, children can ''hide'' their emotion by changing their facial expression as early as age 3 (e.g., Lewis, Stanger, & Sullivan, 1989). Additionally, temperament and emotion understanding appear to moderate the use of the display rules.…”
Section: Other Emotion Regulation Processes: Normative Populationsmentioning
confidence: 99%
“…Children as young as 3 exhibit some use of display rules (e.g., Cole, 1986), with girls doing so more frequently than boys (e.g., Davis, 1995). Relatedly, children can ''hide'' their emotion by changing their facial expression as early as age 3 (e.g., Lewis, Stanger, & Sullivan, 1989). Additionally, temperament and emotion understanding appear to moderate the use of the display rules.…”
Section: Other Emotion Regulation Processes: Normative Populationsmentioning
confidence: 99%
“…It is well-established that verbal deception is evident in children as young as three years old (Chandler, Fritz, & Hala, 1989;Fu, Evans, & Lee, 2012;Lewis, Stanger, & Sullivan, 1989; also Lee & Evans, in press, for a review). Lying abilities improve with age , with several researchers pointing to the development of false belief-understanding another's perspective, as one explanation for this improvement (Chandler et al, 1989;Polak & Harris, 1999;Talwar, Gordon, Lee, 2007;Talwar & Lee, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A commonly used paradigm to investigate verbal deception is the temptation resistance paradigm (Lewis et al, 1989;Polak & Harris, 1999). The researcher instructs the child not to look at a specific, and often desirable, object, such as a toy, placed behind the child's chair.…”
Section: Introductionmentioning
confidence: 99%
“…Third, it is possible that children learn to associate avoidant gaze with lying from their direct experience of deception "in the playground." Although young children and adults do not appear to avoid mutual gaze when they lie (Kleinke, 1986;Lewis, Stranger, & Sullivan, 1989;Talwar & Lee, 2002), a recent study has found that 7-to 9-year-olds do display this behavior (McCarthy, Muir, & Lee, 2007). Accordingly, at 9 years old, children will have had greater opportunity to observe the co-occurrence of gaze aversion and lying in their peers than at 6 years old.…”
Section: Discussionmentioning
confidence: 99%